Credit Point Calculation Model of Functional Position(Case Study of Credit Point Designing for Education Management Quality Assessor at the First Level in Formal Education Institution) - et. al., Gofur Ahmad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to obtain the credit point calculation model for proposing a new functional position within government agencies. The result of the study shows that the calculation phase of the credit point of new functional Position, after the entire procedures for preparing the academic manuscript, preparation of the activity item matrix, validation, and the formulation of the implementation framework is conducted then analysing the calculation with the steps: (1) preparation of activity item matrix, (2) distribution of workload questionnaires and workload analysis, (3) recap tabulation of overall calculation result, (4) analysis of work volume and average time, (5) validation of calculation result, and (6) calculation of credit point. From the result of the study, it is known that the credit point for item 1, that is "compiling a plan for assessing the education management quality " get a credit score of 2.210, while for item 2, which is "designing parameters for measuring the education management quality" gets credit score of 2.605.